Function and layout of the Amsterdam dwelling based on a number of sixteenth-century estate inventories (Bulletin KNOB, 2016)
Apart from a keen interest in materials, constructions and dating, Dutch housing research of the past fifty years has been dominated by a typological approach in which the typology of a house is equated with the floor plan, in combination with the external appearance of the building volume. In 2014 this approach was severely criticized in the doctoral thesis of Petra Maclot, who pointed out that it had led to untenable generalizations and ignores the functional use of the dwellings and their social ranking. This article investigates how sixteenth-century Amsterdam houses were laid out and used by residents from various social classes and occupational groups. The aim is to shed light on what spatial solutions existed for giving form to housing requirements. The estate inventories of the possessions of Amsterdam residents who had fled the city for religious reasons, drawn up in 1567 and 1568 at the behest of the city administration, are an especially rich source of information, owing to the inclusion of a great many spatial indications. These inventories, when combined with details of the occupation and social status of the residents and with details of the material manifestation of the house, provide insight into the internal spatial structure and use of a number of houses. The study looked at the possibility of accommodating various functions in the houses and examined how multifunctional and monofunctional spaces were used by different social groups. In a number of cases, thanks to tax assessment registers and other sources, it was possible to discover which houses these inventories referred to and their rental value. This was an important aid in assessing whether the spatial manifestation of the house could indeed be hooglinked to a social category or occupational group, and in ascertaining to what extent the value of the house was representative of the occupational group in question. A division into three income brackets helps to make a rough classification of houses and their users, although it does have a few important drawbacks. Chief of these is the place where the house stands; one neighbourhood is more expensive than another, with the result that a small house in such a neighbourhood is considerably more expensive than a comparable house in a less attractive location. Thus occupational group and income are not definitive indicators of the physical form of the resident’s house. Estate inventories, combined with the occupation of the owner or resident and the rental value of the house, obviously provide greater insight into the appearance and status of the individual house and make it possible to recognize differences between houses that would appear to be roughly equivalent in spatial–typological terms. Research into spatial indications – and ideally into the space itself, if that is possible in the context of building history research – will in turn help our understanding of the layout of the house. The details that can be obtained from the estate inventories show the degree to which the traditional typological and material-based approach to the dwelling tells only part of the story with respect to a broad understanding of the dwelling in history. In the past in Amsterdam, building history details have usually been conceived as material phenomena, without further classification according to time, place and social significance. A functional approach to the dwelling in its social context is therefore urgently needed.